As micro e pequenas empresas (MPE s) e a função social da licitação - Stroppa, Christianne de Carvalho (2013)
Bidding has always been seen as an instrumental activity of the State. However, with the term of the 1988 Federal Constitution, its legal nature begins to undergo profound changes. This is because one of the foundations of our legal and constitutional is the idea of social function. In the pursuit of social function, the state realizes that by using the bid, it may present as an activity of sustainable economic development, employment generation and income for a large portion of society and the eradication of poverty. This new function of the institute "bid" received from the federal government to use the name of the purchasing power of the State. In using this purchasing power, the state seeks to regulate the market. With that, the bidding stops being one of the support activities of the state, becoming one of its core activities more relevant. The aim of this study was to demonstrate that the different legal status and privileged established by Complementary Law nº 123/2006, in its articles 42-49, microenterprises and small businesses was responsible for the change of the legal nature of the bidding